FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DASAR DI DUSUN MELATI DESA TEBAS SUNGAI KABUPATEN SAMBAS - Rubifar, Zevi; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title is "Drop Factors Causing Primary School in Melati Hamlet, Tebas River Village, Sambas Regency". This research is intended to find out (1) internal factors causing elementary school dropouts in Melati Hamlet, Tebas Sungai Village, and (2) external causes of elementary school dropouts in Melati Hamlet, Tebas Sungai Village. This research uses descriptive qualitative types. The data collection tool uses observation guidelines, interview guidelines and documentation studies. (1) internal factors because of the low interest of children in schooling, (2) external factors causing elementary school dropouts include : (a) economic ability of low parents, most of the income of parents in Melati Hamlet, Tebas Village is only enough to meet their daily needs, (insights will mean children's education) is not a contributing factor, because it is most low educated parents in Melati Hamlet Tebas Sungai Village still wants to continue its education, (c) peer factors are the causes, because most of the environments where live children and their peers drop out from Elementary School have a low education budget and have worked.       Keywords: School Dropouts, Primary School.